2016
DOI: 10.1096/fj.201600392rr
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 regulates inflammasome activation in cholestatic liver injury

Abstract: Macrophage activation is an important feature of primary biliary cholangitis (PBC) pathogenesis and other cholestatic liver diseases. Galectin‐3 (Gal3), a pleiotropic lectin, is produced by monocytic cells and macrophages. However, its role in PBC has not been addressed. We hypothesized that Gal3 is a key to induce NOD‐like receptor family, pyrin domain containing 3 (NLRP3) inflammasome in macrophages and in turn to propagate proinflammatory IL‐17 signaling. In liver tissues from patients with PBC and dnTGF‐βR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 53 publications
8
53
1
1
Order By: Relevance
“…The intraperitoneal administration of MCC950, a specific small molecule inhibitor of NLRP3, resulted in the amelioration of liver injury, survival and fibrosis in BDL-treated mice, strongly supporting a possible therapeutic modulation of the inflammasome [97]. Previous studies have shown that Galectin-3, a lectin produced by macrophages, may activate the NLRP3 inflammasome in the liver and contribute to collagen deposition in a murine model of cholestasis [98]. Interestingly, treatment of mice with Davanat, a registered inhibitor of Galectin-3 that is currently being studied in clinical trials, determined a significant reduction in inflammasome activation and biliary damage in a model of autoimmune cholangitis [99].…”
Section: Inflammasome Activation In Cholestatic Liver Injurymentioning
confidence: 81%
“…The intraperitoneal administration of MCC950, a specific small molecule inhibitor of NLRP3, resulted in the amelioration of liver injury, survival and fibrosis in BDL-treated mice, strongly supporting a possible therapeutic modulation of the inflammasome [97]. Previous studies have shown that Galectin-3, a lectin produced by macrophages, may activate the NLRP3 inflammasome in the liver and contribute to collagen deposition in a murine model of cholestasis [98]. Interestingly, treatment of mice with Davanat, a registered inhibitor of Galectin-3 that is currently being studied in clinical trials, determined a significant reduction in inflammasome activation and biliary damage in a model of autoimmune cholangitis [99].…”
Section: Inflammasome Activation In Cholestatic Liver Injurymentioning
confidence: 81%
“…In addition, Galectin-3 (Gal3), a macrophage produced lectin that was thought to be mediating activation of the inflammasome, was also increased on both the mRNA and the protein levels in these patients. Immunostaining of Gal-3 and NLFP3 were increased in liver sections but whether they were in macrophages or stellate cells was not clear (104). Thus, the role of inflammasomes in cholestatic liver injury remains elusive both in cholestataic animal models and in man and needs much further study.…”
Section: The Role Of the Inflammasome In Cholestatic Liver Injurymentioning
confidence: 99%
“…In a secreted form, galectin‐3 elicits diverse biological responses that include adhesion of tumour cells to the vascular endothelium and activation of specific cell surface receptors such as Toll‐like receptor 4 . Exposure to galectin‐3 also exerts cytokine‐like regulatory actions and, indeed, promotes secretion of IL‐1 β in monocytes, macrophages and microglia . Interestingly, in our study, we found that exogenous galectin‐3 itself did not affect the levels of IL‐1 β , instead acting as an amplifier of the IL‐1 β ‐mediated inflammatory response.…”
Section: Discussionmentioning
confidence: 47%